1993
DOI: 10.1037/0735-7044.107.3.530
|View full text |Cite
|
Sign up to set email alerts
|

Interpositus lesion abolition of the eyeblink conditioned response is not due to effects on performance.

Abstract: Classical conditioning of the rabbit eyeblink response was used to study the effects of cerebellar lesions on performance in animals trained with low-intensity unconditioned stimuli (US). Animals were trained with 1 of 2 low-intensity corneal-airpuff USs paired with a tone-conditioned stimulus. This study confirms earlier findings demonstrating the differential effects of lesions of deep cerebellar nuclei on the conditioned (CR) and unconditioned responses (UR). Lesions of the anterior interpositus nucleus of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…Substantial lesions in the region of the accessory abducens nucleus cause virtual abolition of the NM extension response for both the CR and the UR, but the NM CR shows much greater recovery over time than does the NM UR (Disterhoft et al 1985;Steinmetz et al 1992a). Importantly, lesions of the cerebellum that completely and permanently abolish all components of the CR (see below) have no lasting effect on any component of the UR, at any level of US intensity, including threshold (Steinmetz et al 1992a;Ivkovich et al 1993). The cerebellar circuitry thus plays no essential role in performance of the reflex response.…”
Section: The Ur Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial lesions in the region of the accessory abducens nucleus cause virtual abolition of the NM extension response for both the CR and the UR, but the NM CR shows much greater recovery over time than does the NM UR (Disterhoft et al 1985;Steinmetz et al 1992a). Importantly, lesions of the cerebellum that completely and permanently abolish all components of the CR (see below) have no lasting effect on any component of the UR, at any level of US intensity, including threshold (Steinmetz et al 1992a;Ivkovich et al 1993). The cerebellar circuitry thus plays no essential role in performance of the reflex response.…”
Section: The Ur Pathwaysmentioning
confidence: 99%
“…Steinmetz et al (1992a) investigated numerous parameters of the UR including amplitude, rise time, frequency, and latency in the same animals at several US intensities and found no significant lasting effects of interpositus lesions in any of these properties. Ivkovich et al (1993) lowered US intensity levels to threshold to control for discrepancies in the amplitude of prelesion CRs and URs, and it was again shown that interpositus lesions that completely abolished the CR had no significant effect on postlesion UR amplitude. Results from Kolb et al (1997) have shown similar transient effects on unconditioned limb withdrawal with interpositus inactivation following classical conditioning of this reflex in cats, but again only 130 trials were given during inactivation, and therefore the results cannot be interpreted as demonstrating a sustained involvement of the interpositus on UR expression.…”
Section: The Ur Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators describe a CR loss with a smaller effect on reflex blinks (Bracha et al 1994;Jimenez-Diaz et al 2004;Welsh 1992;Welsh and Harvey 1989). Other investigators report a loss of CRs with no change in reflex blinks (Ivkovich et al 1993;McCormick and Thompson 1984;Steinmetz et al 1992). These divergent results may arise from differences in the anterior-posterior extent of IP lesions and the collection of data immediately after IP inactivation (Bracha et al 1994;Jimenez-Diaz et al 2004) rather than days after the lesion (Ivkovich et al 1993;McCormick and Thompson 1984;Steinmetz et al 1992 (Chen and Evinger 2006;Jimenez-Diaz et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Lesions of the interpositus nucleus completely and permanently abolish previously learned conditioned responding (Steinmetz & Sengelaub, 1992) and block acquisition in naive animals (McCormick & Thompson, 1982), with no significant effects on performance of the reflex itself (Ivkovich, Lockard, & Thompson, 1993). Lesions of the cerebellar cortex disrupt conditioning, but small-amplitude, poorly timed conditioned responses do slowly develop across training (Lavond et al, 1987;Woodruff-Pak, Lavond, Logan, Steinmetz, & Thompson, 1993).…”
Section: The Cerebellum and Classical Conditioningmentioning
confidence: 99%